Historical comparisons between of human and canine case reports of Visceral Leishmanisis in Colombia according to the one health approach: paper review - Caicedo Blanco, Yuly Andrea; Parada Pinilla, Valentina; Hernández Peña, Santiago; Wongchuig Correa, Sly (Spei Domus, 2022)
One of the zoonoses of great impact is the visceral Leishmaniasis caused by the protozoan parasite Leishmania infantum, transmitted by the infected hematophagous female vector called Lutzomyia longipalpis, the main reservoir being the domestic dog, considered a forgotten tropical pathology in 98 countries worldwide, especially in Colombia since its first cases in humans and dogs. The objective of the work was to develop a systematic review of the literature about the epidemiological behavior of Visceral Leishmaniasis over the years in Colombia, using three recognized databases (Academic Google, PubMed and Dialnet) as well as the Mendeley and Other bibliographic sources, initially 180,610 documents were found, of which 21,673 duplicates were eliminated, leaving 158,937 studies remaining, later a third selection of 11,127 articles was made and finally 126 selected articles cover the topics of interest. The distribution of cases of the disease ranges from the Magdalena River Valley such as Huila, Tolima to the departments of Sucre and Córdoba with a high frequency, it is also highlighted that in canines the data on the occurrence are not updated due to the lack of studies. In conclusion, visceral Leishmaniasis is considered an epidemiological and public health problem due to the contact between the main reservoir and man. In Colombia over the years it has been found that the data on reports in humans has been developed without interruptions in the areas of greatest risk (Sucre, Córdoba, Santander, Tolima, Huila) while in canines the search and notification has not been specific and even incomplete, presenting limitations at the time of determining the current occurrence of the disease, therefore It is therefore essential to strengthen surveillance systems to generate truthful information on cases depending directly on the knowledge of VL by veterinarians and responsible entities.